Postural assessment software (PAS/SAPO): validation and reliabiliy (Clinics, 2010)
OBJECTIVE: This study was designed to estimate the accuracy of the postural assessment software (PAS/SAPO) for measurement of corporal angles and distances as well as the inter- and intra-rater reliabilities. INTRODUCTION: Postural assessment software was developed as a subsidiary tool for postural assessment. It is easy to use and available in the public domain. Nonetheless, validation studies are lacking. METHODS: The study sample consisted of 88 pictures from 22 subjects, and each subject was assessed twice (1 week interval) by 5 blinded raters. Inter- and intra-rater reliabilities were estimated using the intraclass correlation coefficient. To estimate the accuracy of the software, an inanimate object was marked with hallmarks using pre-established parameters. Pictures of the object were rated, and values were checked against the known parameters. RESULTS: Inter-rater reliability was excellent for 41% of the variables and very good for 35%. Ten percent of the variables had acceptable reliability, and 14% were defined as non-acceptable. For intra-rater reliability, 44.8% of the measurements were considered to be excellent, 23.5% were very good, 12.4% were acceptable and 19.3% were considered non-acceptable. Angular measurements had a mean error analisys of 0.11°, and the mean error analisys for distance was 1.8 mm. DISCUSSION: Unacceptable intraclass correlation coefficient values typically used the vertical line as a reference, and this may have increased the inaccuracy of the estimates. Increased accuracies were obtained by younger raters with more sophisticated computer skills, suggesting that past experience influenced results. CONCLUSION: The postural assessment software was accurate for measuring corporal angles and distances and should be considered as a reliable tool for postural assessment.